Effects of Boron and Molybdenum on the Yield of Chickpea - Shil, NC; Noor, S; Hossain, MA (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Field experiments on chickpea (cv. BARI Chola-5) were carried out in Calcareous Dark Grey Floodplain Soil under AEZ 11 at Jessore and Non Calcareous Grey Floodplain Soil under AEZ 13 at Rahmatpur during the rabi season of 2001-2002 and 2002-2003. The objective was to find out the optimum dose of boron and molybdenum for yield maximization. Four levels each of boron (0, 1, 2 and 2.5 kg/ha) and molybdenum (0, 1, 1.5 and 2 kg/ha) along with a blanket dose of N20 P25 K35 S20 Zn2 kg/ha & cowdung 5 t/ha were applied in this study. The combination of B2.5 Mo1.5 kg/ha and B2.5 Mo1 kg/ha produced significantly higher yield in both the years of study at Jessore and Rahmatpur, respectively. The said treatments produced the highest mean yields of 2.10 and 1.49 t/ha for Jessore and Rahmatpur, respectively, which was around 53% higher over control (B0 M0). The combined application of both boron and molybdenum were found superior to their single application even though boron played major role in augmenting the yield. However, from the regression analysis, the optimum treatment combination was calculated as B2.34 Mo1.44 kg/ha for Jessore and B2.20 Mo1.29 kg/ha for Rahmatpur. Key words: Boron, molybdenum, chickpea, yield, flood plain soil. DOI = 10.3329/jard.v5i1.1452 J Agric Rural Dev 5(1&2), 17-24, June 2007